2020
DOI: 10.1002/cbin.11526
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stem cells microvesicles stabilize atherosclerotic plaques by inhibiting NLRP3‐mediated macrophage pyroptosis

Abstract: Rupture of atherosclerotic plaques constitutes the major cause of thrombosis and acute ischemic coronary syndrome. Bone marrow‐derived mesenchymal stem cells microvesicles (BMSCs‐MVs) are reported to promote angiogenesis. This study investigated the role of BMSCs‐MVs in stabilizing atherosclerotic plaques. BMSCs‐MVs in mice were isolated and identified. The mouse model of atherosclerosis was established, and mice were injected with BMSCs‐MVs via the tail vein. The macrophage model with high glucose and oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…When p65 is silenced with siRNA, the nicotine-induced protein expression of cleaved Caspase1, IL-1β, IL-18 are decreased remarkably in RAW264.7 cells (Xu et al, 2021). Moreover, experimental data confirms that ox-LDL activates the NLRP3-mediated pyroptosis pathway in macrophages (Lin et al, 2020;Mu et al, 2020). Peng et al reported that mitochondrial outer membrane protein NIX inhibits ox-LDL-induced macrophages pyroptosis by activating mitophagy.…”
Section: Pyroptosis In the Progression Of Atherosclerosismentioning
confidence: 87%
See 1 more Smart Citation
“…When p65 is silenced with siRNA, the nicotine-induced protein expression of cleaved Caspase1, IL-1β, IL-18 are decreased remarkably in RAW264.7 cells (Xu et al, 2021). Moreover, experimental data confirms that ox-LDL activates the NLRP3-mediated pyroptosis pathway in macrophages (Lin et al, 2020;Mu et al, 2020). Peng et al reported that mitochondrial outer membrane protein NIX inhibits ox-LDL-induced macrophages pyroptosis by activating mitophagy.…”
Section: Pyroptosis In the Progression Of Atherosclerosismentioning
confidence: 87%
“…The latest research confirms that PIC up-regulates miR-200a and Nrf2 to inhibit macrophage pyroptosis and ultimately alleviate atherosclerosis ( Mu et al, 2020 ). The study of bone marrow-derived mesenchymal stem cells microvesicles (BMSCs-MVs) on the treatment of atherosclerosis in mice showed that miR-223 inhibited macrophages pyroptosis by reducing the expression of NLRP3 ( Lin et al, 2020 ). Non-coding RNA-dependent way will become the new treatment ideas of atherosclerosis.…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…Subsequently, Varghese et al also demonstrated the close relationship between the upregulation of NLRP3 inflammasome-related components and plaque vulnerability, suggesting the possibility of NLRP3 inflammasome activation in promoting plaque instability ( Paramel Varghese et al, 2016 ). Inhibiting NLRP3 expression and reducing macrophage pyroptosis could stabilize atherosclerotic plaques, which undoubtedly hinted at the potential value of blocking pyroptosis ( Lin et al, 2021 ).…”
Section: The Roles Of Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…As another natural antiatherosclerotic drug, piceatannol suppressed pyroptosis and oxLDL‐induced lipid storage in macrophages via regulating miR‐200a/Nrf2/GSDMD signaling (Mu et al, 2020). Another study reported that miR‐223 carried by bone marrow‐derived mesenchymal stem cells microvesicles stabilized the atherosclerotic plaques by reducing macrophage pyroptosis (Y. Lin et al, 2020). Circular RNAs (circRNAs) are a group of ncRNAs characterized by a covalently closed loop.…”
Section: Role Of Pyroptosis In Atherosclerosismentioning
confidence: 99%